Expedient Access to Structural Complexity via Radical β-Fragmentation of N–O Bonds - Yang, Xingheng; Zhang, Chi; Wang, Cheng-Qiang; Feng, Chao (Synlett, 2025)
Structures containing N–O bonds are well-established precursors of nitrogen- and/or oxygen-centered radicals under visible-light conditions in modern organic synthesis. Whereas both heterolytic and homolytic scissions of N–O bonds have been extensively documented, intrinsic limitations related to substrate structure somewhat restrict their broader application. This paper highlights a novel strategy that synergistically combines a radical-generation process that is independent of the substrate’s redox potential with a radical-induced β-fragmentation of the N–O bond. Subsequent manipulation of the generated nitrogen- or oxygen-centered radicals leads to the successful development of group-transfer carboamination of alkenes, ring-opening functionalization of heterocycles, and efficient trifunctionalization of nonactivated alkenes.1 Introduction2 Carboamination of Nonactivated Alkenes3 Radical-Addition-Induced Ring-Opening Functionalization of 4-Isoxazolines4 Multisite Functionalization of Alkenes by Merging Cycloaddition and Ring-Opening Functionalization5 Conclusion
Keywords: β-fragmentation; N–O bond scission; radical reactions; halogen-atom transfer; remote functionalization